Stimulation of Cellular Thymidine Kinases by Human Cytomegalovirus - Estes, John E. (1977)
Thymidine kinase (TK) activity in WI-38 and MRC-5 human fibroblasts was analyzed by discontinuous polyacrylamide gel electrophoresis (disc-PAGE) and discontinuous glycerol gradient electrophoresis (disc-GEP) after subculture or human cytomegalovirus (HCMV) infection. Two peaks of TK activity with different relative fraction-of-migration (R(f)) values were resolved by disc-PAGE or disc-GEP in extracts from log-phase and infected cells. Growing WI-38 cells expressed a slowly migrating (R(f) = 0.14 PAGE, R(f) = 0.4 GEP) peak of TK activity, which was partially inhibited by 1.0 mM dCTP, but which retained little activity at pH 4.5. Growing MRC cells also displayed a slowly migrating peak (R(f) = 0.10 PAGE) with similar properties. Both cell types expressed a faster-migrating TK activity (R(f) = 0.45 PAGE, R(f) = 0.7 GEP) in the growing and resting state that was strongly inhibited by 1 mM dCTP but retained 50% activity at pH 4.5. When either cell type was infected with HCMV, there was a rapid and high-level stimulation of the slowly migrating form of TK and a slight stimulation of the faster-migrating form. Two strains of HCMV (AD169 and Town) failed to produce an electrophoretically distinct virus TK in either cell type after infection. TK enzymes were partially purified by disc-GEP from extracts of log-phase WI-38 or AD169-infected WI-38 cells. Characterization of these enzymes with respect to phosphate donor specificity, pH optima, thermostability, and salt inhibition showed the HCMV-stimulated TKs to be of cellular origin.